Biomechanical behavior of modular acetabular cups made of poly-ether-ether-ketone: A finite element study. (October 2018) - Vogel, Danny; Schulze, Christian; Dempwolf, Henry; Kluess, Daniel; Bader, Rainer
After total hip arthroplasty, stress-shielding is a potential risk factor for aseptic loosening of acetabular cups made of metals. This might be avoided by the use of acetabular cups made of implant materials with lower stiffness. The purpose of this numerical study was to determine whether a modular acetabular cup with a shell made of poly-ether-ether-ketone or poly-ether-ether-ketone reinforced with carbon fibers might be an alternative to conventional metallic shells. Therefore, the press-fit implantation of modular cups with shells made of different materials (Ti6Al4V, poly-ether-ether-ketone, and poly-ether-ether-ketone reinforced with carbon fibers) and varying liner materials (ceramics and ultra-high-molecular-weight polyethylene) into an artificial bone cavity was simulated using finite element analysis. The shell material had a major impact on the radial shell deformation determined at the rim of the shell, ranging from 17.9 µm for titanium over 92.2 µm for poly-ether-ether-ketone reinforced with carbon fibers up to 475.9 µm for poly-ether-ether-ketone. Larger radial liner deformations (up to 618.4 µm) occurred in combination with the shells made of poly-ether-ether-ketone compared to titanium and poly-ether-ether-ketone reinforced with carbon fibers. Hence, it can be stated that conventional poly-ether-ether-ketone is not a suitable shell material for modular acetabular cups. However, the radial shell deformation can be reduced if the poly-ether-ether-ketone reinforced with carbon fiber material is used, while deformation of ceramic liners is similar to the deformation in combination with titanium shells.